Cardiovascular Risk in Rheumatic Patients: The Link between Inflammation and Atherothrombosis - Di Minno, Matteo Nicola Dario; Iervolino, Salvatore; Lupoli, Roberta; Russolillo, Anna; Coppola, Antonio; Peluso, Rosario; Scarpa, Raffaele; Di Minno, Giovanni (Seminars in Thrombosis and Hemostasis, 2012)
In addition to a high prevalence of the metabolic syndrome and a significant under-diagnosis of vascular risk factors (VRFs), the effect of chronic inflammation also represents the cornerstone of the raised cardiovascular (CV) risk in patients with rheumatoid arthritis, psoriatic arthritis, and ankylosing spondylitis. Moreover, the finding that among current anti-inflammatory treatments, the use of tumor necrosis factor (TNF)-α blockers is associated with optimal rheumatologic and CV outcomes further supports the impact of inflammation on the CV risk. However, up-to-date treatment guidelines suggest that TNF-α blockers should be used only after the failure of traditional disease-modifying antirheumatic drugs (DMARDs). Early predictors of the therapeutic efficacy of traditional DMARDs are needed to identify candidates for TNF-α blocker treatment. Furthermore, whether the CV risk should be taken into account while choosing antirheumatic treatments is an emerging issue to be addressed. Common educational programs for specialists and general practitioners and appropriate CV prevention programs, taking into consideration traditional VRFs as well as the inflammatory status, should be planned to prevent ischemic events and to achieve optimal inflammation control in rheumatic patients.
Keywords: cardiovascular risk; rheumatoid arthritis; psoriatic arthritis; ankylosing spondylitis